Síntesis y caracterización de puntos cuánticos de carbono a partir de desechos de levadura cervecera (2020)
Carbon quantum dots (PCs) are newly discovered photoluminescent nanoparticles and the latest research has grown tremendously over years. Its optical properties, biocompatibility and particle size between 2-20 nm make them ideal nanomaterials for applications in biotechnology and medicine. In addition, the ease of synthesis of these particles using any carbonaceous precursor provides an opportunity to the food industry and take advantage of carbon-based residues to give them added value. In the present work, the synthesis of carbon quantum dots is carried out using Saccharomyces cerevisiae yeast as organic precursor, from the waste of Bavaria S.A beer industry production. The nanoparticles were synthesized using two methods, thermal decomposition via pyrolysis and in muffle. These were purified and later characterized to determine the properties of fluorescence, size distribution and composition of the material. Finally, the carbon quantum dots were obtained and the effectiveness of both synthesis protocols was confirmed, although the decomposition...